Knowledge, utilization and barriers to primary care services for sexual and reproductive health among adolescents in secondary schools in selangor, Malaysia - Othman, Sajaratulnisah; Zin, Kong Sie; Mydin, Fadzilah Hanum Mohd; Ng, Chirk Jenn (Academy of Family Physicians of Malaysia, 2019)
Early sexual debut, partner violence, pregnancy and sexually transmitted infections contribute to negative health outcomes among adolescents. While the primary care clinics offer accessible sexual and reproductive health (SRH) services to adolescents, it is uncertain whether adolescents are aware of and utilize these services. This study aimed to examine Malaysian adolescents’ knowledge, utilization and barriers to primary care services for SRH. A cross-sectional survey was conducted from August to November 2011 among adolescent from five randomly selected schools in Selangor, Malaysia. A self-administered questionnaire was used to assess their knowledge, attitudes, sexual behaviors and utilization of SRH services. A total of 680 adolescents participated in the study. One in ten of the adolescents were aware of the availability of SRH services, and only 6.9% of them had ever visited a primary care clinic for SRH. About 75% of them felt uncomfortable going to a primary care clinic for SRH services. Knowledge and utilization of primary care clinics for SRH among adolescents in Malaysia is poor. © 2019 Malaysian Family Physician. All rights reserved.